(untitled) - Lawrence, D. H. (Cambridge [U.K.],New York, 1999)
D. H. Lawrence wrote his last novel, Lady Chatterley's Lover, three times, and it is the third version that has become famous. The three versions are in fact three different novels, varying in length, significant episodes, and even some of the main characters. This is the first critical edition of the two early versions of the novel. The text is printed from manuscript source, including numerous deletions and variations from early printed editions. An introduction traces the genesis, publication and reception of the novel, and there are detailed explanatory notes.
Keywords: Married women,Lady Chatterley's lover,Phụ nữ đã kết hôn, Người yêu của quý bà Chatterley; Fiction,Criticism, Textual.,Tiểu thuyết,Nguyên bản, phê bình